Pelatihan Peningkatan Kemampuan Menulis Huruf Hijaiyyah Bagi Anak Usia Dini di TPQ Al-Hikmah - Widyaningsih, Bekti; Hidayatulloh, Muhammad Kris Yuan; Mujahid, Bagas Ibnu (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2024)
The majority of Miagan Village residents are Muslim, but in terms of implementation in daily life, they are quite low in participating in Islamic activities organized by the Village. This is a problem where some residents are still low in knowledge of jurisprudence which is the basis of Islam, one small example of which is related to the ability to write hijaiyah letters. This problem needs to be resolved through community service activities. The objectives of this service activity include: a) providing training to TPQ santri students on how to write hijaiyyah letters well b) providing an understanding of how to write hijaiyyah letters with meaning and connecting hijaiyyah letters well c) making a guidebook and reading and writing exercises al-Qur'an d) provide motivation to TPQ students in learning the basic science of reading and writing the Al-Qur'an properly and correctly. This service activity was carried out at TPQ Al-Hikmah Miagan Village, Mojoagung District on September 19 2023 at 16.00-17.00 and was attended by all students of TPQ Al-Hikmah Miagan Village. This activity was filled with introduction and training in reading and writing the Al-Quran. This service activity uses discussion and training methods. The service activity produced a book that is proficient in Arabic writing for beginners which has an impact on the knowledge of the TPQ Al Hikmah students. Because, it is able to help TPQ Al Hikmah students to make it easier to write Arabic correctly, as well as increase insight/knowledge in the students' learning process. Apart from that, this book can improve the skills of students, because the contents of the book prioritize practice/exercise rather than theory.